Peningkatan Karakter Jujur: Studi Pengaruh Layanan BK Kelasikal PKC-KA Strategi BMB3 - Famahato Lase (Journal on Education, 2024)
Students' honest character can be formed, developed and enhanced with various guidance and counseling services. The aim of this research is to see the influence and contribution of the independent variable to the dependent variable using associative quantitative methods. The research population was all students of the BK FKIP study program at Nias University and a sample of 44 people was drawn in the fourth semester. The data collection instrument was a closed questionnaire and was analyzed using multiple linear regression statistical techniques. The research results reveal that: there is a partially significant influence of the Classical Counseling service (X1) on increasing honest character (Y) and every increase in X1 of 1.00% will be followed by an increase in Y of 0.27%; there is a partially significant influence of intelligent character education in the classical format (X2) on increasing Y and every increase in X2 of 1.00% will be followed by an increase in Y of 0.328; there is a partially significant influence of the BMB3 (X3) strategy on increasing Y and every increase in X3 of 1.00% will be followed by an increase in Y of 0.625; and (4) there is a significant influence of the variables X1, It is recommended that counseling guidance lecturers provide this service to improve students' honest character.